Associations of Adenovirus Genotypes in Korean Acute Gastroenteritis Patients with Respiratory Symptoms and Intussusception. (1st February 2017) - Kim, Jae-Seok; Lee, Su Kyung; Ko, Dae-Hyun; Hyun, Jungwon; Kim, Han-Sung; Song, Wonkeun; Kim, Hyun Soo
Abstract : Human adenoviruses (HAdVs) cause a wide range of diseases, including respiratory infections and gastroenteritis, and have more than 65 genotypes. To investigate the current genotypes of circulating HAdV strains, we performed molecular genotyping of HAdVs in the stool from patients with acute gastroenteritis and tried to determine their associations with clinical symptoms. From June 2014 to May 2016, 3, 901 fecal samples were tested for an AdV antigen, and 254 samples (6.5%) yielded positive results. Genotyping using PCR and sequencing of the capsid hexon gene was performed for 236 AdV antigen-positive fecal specimens. HAdV-41, of species F, was the most prevalent genotype (60.6%), followed by HAdV-2 of species C (13.8%). Other genotypes, including HAdV-3, HAdV-1, HAdV-5, HAdV-6, HAdV-31, HAdV-40, HAdV-12, and HAdV-55, were also detected. Overall, 119 patients (50.4%) showed concomitant respiratory symptoms, and 32 patients (13.6%) were diagnosed with intussusception. HAdV-1 and HAdV-31 were significantly associated with intussusception (P < 0.05 ). Our results demonstrate the recent changes in trends of circulating AdV genotypes associated with gastroenteritis in Korea, which should be of value for improving the diagnosis and developing new detection, treatment, and prevention strategies for broad application in clinical laboratories.